Webb, Heather (2022), Dante, Artist of Gesture. Oxford: Oxford University Press. 208 pp. ISBN: 9780192866998 y eISBN: 9780191959202 - Vilella, Eduard (Revista de Literatura Medieval, 2024)
Reseña a Webb, Heather (2022), Dante, Artist of Gesture. Oxford: Oxford University Press.